Integration of Artificial Intelligence in Personal Financial Management: A Study of Adaptive System Development for the Digital Generation - Fauziah, Nayla; Sulistianingsih, Henny; Sari, Vina Delta (Jurnal Penelitian Dan Pengkajian Ilmiah Eksakta, 2025)
The digital transformation era presents new challenges in personal financial management, particularly for millennials and Gen Z, who are prone to consumptive behavior, the Fear of Missing Out (FOMO), and low financial literacy. This study aims to explore the potential development of an adaptive system based on artificial intelligence to improve the effectiveness of personal finance management. Using a qualitative approach through literature and bibliometric analysis, the study employs VOSviewer to identify dominant themes such as financial behavior, financial education, and personal financial planning, with limited representation of AI integration and adaptive systems. This indicates a research gap that offers strategic opportunities for innovation in finance systems. The study formulates the need for intelligent features such as spending pattern analysis, personalized financial recommendations, and automatic adjustments based on user profiles. These findings are expected to serve as a conceptual foundation for developing smarter and more adaptive personal finance systems aligned with the characteristics of the digital generation.